The Development of PC-Based 2D Farming Simulation Role-Playing Game: Tranquil Harvest - Lee, Bing Yang; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2024)
Agriculture, essential for human civilization, faces disconnection due to urbanization. To bridge this gap, "Tranquil Harvest," a 2D farming simulation RPG for PC, educates players about the variety of vegetables commonly grown in Malaysia. The game offers a virtual farming experience, allowing players to engage in realistic agricultural activities, enhancing their awareness of food origins. Developed using the Game Development Life Cycle (GDLC), the game targets users aged 12 to 35. Alpha testing ensured functionality, while beta testing with 30 participants provided positive feedback on learning outcomes, user acceptance, and functionality. Players found the game educational and enjoyable, demonstrating its effectiveness in bridging the urban-agriculture knowledge gap.